2021
DOI: 10.1021/acs.macromol.1c00650
|View full text |Cite
|
Sign up to set email alerts
|

Complete pH-Dependent Shape Recovery in Cubical Hydrogel Capsules after Large Osmotic Deformations

Abstract: Polymeric colloids with reversible shape transformations have attracted increasing interest as stimuli-responsive biomimetic microsystems. We present cubical poly(methacrylic acid) (PMAA) hydrogel capsules that completely and reversibly collapse in response to osmotic pressure differences induced with poly(styrene sulfonate sodium salt) (PSS). The capsules with nanothin highly hydrated walls are synthesized through a multilayer assembly approach using 5 μm cubical sacrificial templates. The degree of capsule d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…It is, however, less straightforward to determine the single nanogel compressibility and resistance to deformations. This can be achieved by directly imaging the nanogels , or performing scattering experiments at different osmotic pressures set by osmotic stress solutions or by performing AFM. , …”
Section: Softness and Characteristic Lengthsmentioning
confidence: 99%
“…It is, however, less straightforward to determine the single nanogel compressibility and resistance to deformations. This can be achieved by directly imaging the nanogels , or performing scattering experiments at different osmotic pressures set by osmotic stress solutions or by performing AFM. , …”
Section: Softness and Characteristic Lengthsmentioning
confidence: 99%
“…Conversely, a nonspherical shape of a hydrogel particle has been demonstrated to favor the particle passing through pores and channels with smaller-than-particle-size diameters . In our work on the multilayer hydrogel capsules, we have demonstrated that despite the inherent softness and high swelling of the capsule wall, the nonspherical multilayer hydrogel capsules with the shape of nonspherical template particles can be obtained after template dissolution. ,, …”
Section: Synthesis Of Two-dimensional and Three-dimensional Multilaye...mentioning
confidence: 77%
“…The cubical PMAA multilayer network capsules were synthesized as hydrogel replicas of cubic MnCO 3 microparticles (4 to 5 μm) through the chemical cross-linking of hydrogen-bonded multilayer films of PMAA and PVPON . Single-component (PMAA) 20 capsules with a 20-layer hydrogel wall were produced either by cross-linking PMAA layers with a bifunctional cross-linker or by using a PMAA-NH 2 copolymer assembled with PVPON, where PMAA-NH 2 layers were covalently bound through carbodiimide-assisted cross-linking, resulting in amide linkages between amino and carboxylic groups and followed by PVPON release at basic pH. , The two-component (PMAA-PVPON) 5 hydrogel capsules were obtained when PVPON-NH 2 was assembled with PMAA followed by the carbodiimide-assisted binding of PMAA to PVPON-NH 2 layers . Using discoid silicon microparticles with a large aspect ratio as sacrificial templates led to the discoidal hydrogel capsules, either single- or two-component, with the shape of a red blood cell, an erythrocyte …”
Section: Synthesis Of Two-dimensional and Three-dimensional Multilaye...mentioning
confidence: 99%
See 2 more Smart Citations